Thermal Reduction of Common Food-Borne Pathogens During Composting - Cooper, Ashley (Université d'Ottawa / University of Ottawa, 2015)
Soil amended with manure has been implicated as a source of produce contamination leading to foodborne gastrointestinal-disease outbreaks. While current composting guidelines require temperatures ≥ 55°C for 3 days to destroy bacterial pathogens, these requirements have not been evaluated for all pathogens. Investigation of parasite survival in manure required development of a flow cytometry method integrating the cell-impermeant viability dye SytoX for simultaneous quantification and viability assessment of Cryptosporidium and Giardia oocysts/cysts. Further studies will be required to apply this method to investigate thermal reduction in parasites. Studies conducted with bacterial pathogens indicated that E. coli O157:H7 survived longer than other pathogens at 50°C to 55°C. Listeria monocytogenes survived significantly better in chicken manure compared to cow manure at 50°C to 55°C. Results suggest composting guidelines are adequate for bacterial pathogen reduction; however, testing for E. coli O157 along with Salmonella may increase confidence in compost safety.
Keywords: Pathogen; Composting; Thermal reduction; E. coli; Listeria monocytogenes; Salmonella enterica; Giardia; Cryptosporidium; Flow cytometry; D-value; Manure; Campylobacter